Budowanie stałych relacji między małym przedsiębiorstwem a bankiem - Mazur-Łukomska, Karolina; Śnihur, Janusz (Building of Solid Report Among Small Enterprise and Bank, 2005)
Small Companies create relationship with bank to minimize risk of operating in turbulent business environment. There are some reasons for creating such partnership: to minimize risk, to cut some costs and to gain better access to capital. Some threats also appear in such relations: transaction costs and loss of opportunities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 241-247